Sistematic Literature Review: Pengaruh Pengembangan AI (Artificial Inteligence) terhadap Informasi Kesehatan di Indonesia Dari Aspek Ketepatan Dan Aksesibilitas - Rr. Devi Noviana Setyoningsih; Cahya Tri Purnami; Antono Suryoputro (Universitas Malahayati Lampung, 2025)
ABSTRACT The greatest challenge in Indonesia's healthcare sector is the limited number of doctors and their uneven distribution, as well as insufficient health information. One solution being implemented is utilizing artificial intelligence (AI) technology. The development of artificial intelligence has provided significant impact on the healthcare sector, including assisting in disease diagnosis, medical imaging analysis, predicting disease risks and progression, monitoring patient health data, and managing hospital administration. The utilization of AI technology can also improve accessibility, convenience, and accuracy in obtaining information within healthcare delivery systems, including reducing human error and physicians' cognitive bias in determining the best treatment decisions.analyzing the impact of AI development on improving health information in Indonesia from the aspects of accuracy and accessibility. Systematic Literature Review was conducted using a database PubMed, Scopus, Google Scholar, dan Semantic dengan rentang publikasi 2020-2025. Kata kunci yang digunakan meliputi: “pengaruh”,